A high-speed radio-over-free-space optics link using wavelength division multiplexing-mode division multiplexing-multibeam technique. (October 2020) - Balasaraswathi, M.; Singh, Mehtab; Malhotra, Jyoteesh; Dhasarathan, Vigneswaran
Abstract: Radio-over-Free-Space Optics (RoFSO) is a key technology for providing high-speed communication links in rural areas. In this work, an orthogonal frequency division multiplexing based RoFSO transmission link has been designed by adopting hybrid wavelength division multiplexing (WDM), mode division multiplexing (MDM) and multibeam technique. The proposed link is investigated under heavy fog weather conditions and its performance is compared for 1-beam and 4-beams transmission using numerical simulations. The numerical results show faithful transportation of high-speed data at 2000 m with acceptable performance of the link. Furthermore, the link performance is compared with previously reported works and the proposed RoFSO link with hybrid WDM-MDM-multibeam technique demonstrates an enhanced link range and transmission capacity performance.